Genetic knowledge and attitudes towards genetic testing among final-year medical students at a public university in Ecuador - Jaramillo-Aguilar, Damary S.; Simbaña-Rivera, Katherine (Frontiers in Medicine, 2024)
Background: Genetics plays a crucial role in the field of medicine, offering numerous applications. However, health professionals often have insufficient knowledge in this area. Therefore, it is essential to provide appropriate genetics education during university studies.Aim: This study aims to assess the knowledge and attitudes towards genetic testing among final-year medical students at a public university in Ecuador.A cross-sectional study was conducted involving final-year medical students from a public university in Ecuador. The third version of the Genetic Literacy and Attitudes Survey was administered between April and May 2022. The study examined sociodemographic characteristics, genetic knowledge, and attitudes towards genetic testing.The study included 153 medical students, of which 58.2% identified as female. Most participants fell within the age range of 22 to 25 years old (85.0%). Regarding genetic knowledge, three-quarters of the participants (75.2%) demonstrated intermediate proficiency, while only 9.80% possessed a high level of knowledge. Attitudes towards the clinical and therapeutic applications of genetics, scientific advancements, access to conventional medicine, and other related topics were found to be appropriate.The findings suggest that most final-year medical students at a public university in Ecuador have intermediate genetic knowledge and hold appropriate attitudes towards genetic testing. However, higher education institutions should conduct a comprehensive analysis and restructure their curricula to better prepare students for the medical and technological challenges of the 21st century.